Selective oncolytic effect in Epstein-Barr virus (EBV)-associated gastric carcinoma through efficient lytic induction by Euphorbia extracts. (March 2018) - Kim, Dong-eun; Jung, Sunhee; Ryu, Hyung Won; Choi, Miri; Kang, Mingu; Kang, Hyunju; Yuk, Heung Joo; Jeong, Hyejeong; Baek, Jiyeon; Song, Jae-Hyoung; Kim, Janghwan; Kang, Hyojeung; et al.
Highlights: Identification of three Euphorbia extracts with EBV lytic-inducing activity. Euphorbia extracts efficiently induce lytic replication in most of cell population. Euphorbia extracts induce EBV reactivation through modulating PKC/MEK pathway. PMA analogs in Euphorbia extracts contribute to lytic induction of EBV. E. pekinensis extract has an oncolytic effect selectively on EBV-positive gastric carcinoma cells. Abstract: Lytic induction of latent Epstein-Barr virus (EBV) has been considered as a therapeutic approach for efficient treatment of EBV-associated malignancies. Here, we established a robust assay system quantitatively measuring EBV lytic induction and identified three Euphorbia extracts as strong inducers from a screen of Korean medicinal plant extracts library. Expression of lytic genes were efficiently induced by each Euphorbia extract in SNU-719 (EBV-positive gastric carcinoma cells). Euphorbia pekinensis, out of three extracts, exhibited the most potent lytic-inducing activity. Importantly, treatment with E. pekinensis extract led to an obvious cytotoxic effect on SNU-719 cells, but little on MKN-74 cells (EBV-negative gastric carcinoma cells), indicating the selective oncolytic effect on EBV-positive gastric carcinoma. We further revealed that lytic-inducing activity of E. pekinensis was mediated by PKC/MEK signal. Moreover, we defined two structural analogs of PMA with strong lytic-inducing activity, suggesting their therapeutic applicability for the treatment of EBV-associated gastric carcinoma.